The Effect of Size and Board Gender Diversity in Dividend Payout: An Applied Study on Service Shareholding Companies Listed in Amman Stock Exchange - Al Shaar, Ishaq M. (Jordan Journal of Business Administration, 2022)
This study aimed at identifying the effect of board size and board gender diversity on dividend payout and identifying the role of return on assets (ROA) in moderating the effect of size and board gender diversity on dividend payout. The study population consisted of (45) service shareholding companies listed in Amman Stock Exchange (ASE), during the period (2009-2018), using balanced panel data of (36) service companies with (360) observations. The results indicate that the level of female representation in the boards of service companies in Jordan is still low compared to other countries. The results also showed that board size and board gender diversity affect dividend payout. In addition, the return on assets moderates the effect of board size on dividend payout. The results also showed that the return on assets does not moderate the effect of board gender diversity on dividend payout. The study recommends that regulatory bodies should take a step towards encouraging gender diversity in boards to enhance board of directors’ effectiveness, through amending legislations that regulate female participation in boards, such as the Jordanian Corporate Governance Code.